The updated Global Naturalized Alien Flora ( GloNAF 2.0) database - Amy J. S. Davis; Wayne Dawson; Franz Essl; Holger Kreft; Bernd Lenzner; Jan Pergl; Petr Pyšek; Patrick Weigelt; Marten Winter; Mark van Kleunen (Ecology, 2025)
GloNAF is a continuously updated, curated compilation of alien naturalized vascular plant inventories for geographic regions worldwide. Building on its predecessor, GloNAF 2.0 now contains 16,429 taxa and introduces major updates, including the standardization of taxonomic names using the World Checklist of Vascular Plants (WCVP), removal of outdated records, and the net addition of 117,229 new records. These new entries have substantially increased the size of GloNAF, resulting in a 26% increase in the number of naturalized taxa in the database and a 31% increase in the number of geographic regions compared to GloNAF 1.2. We provide an overview of GloNAF 2.0, highlighting its expanded geographic and taxonomic coverage. In addition, we have aligned GloNAF with FAIR data principles through improvements in data accessibility, metadata standards, and support for data reuse. GloNAF 2.0 represents a significant and comprehensive resource for researchers aiming to advance our understanding of the drivers and consequences of biological invasions and naturalization success. The dataset is published under a CC‐BY 4.0 license; thus, when using these data, please give credit to this paper.